Green Metric in Higher Education- Measuring and Reporting on Sustainability Initiatives at Higher Education Institutions - Azuz-Adeath, Isaac; Aguiar, Fernanda; Romero, María Elena; López, Ulises; Valdes, Adrián (SPRINGER Nature link, 2026)
CETYS University is a multicampus (three campuses) private university located in the Northwest corner of Mexico, on the border with California in the United States. The climate in the region goes from arid (Mexicali Campus) to semiarid (Tijuana and Ensenada Campuses) and the most important environmental problems faced by the campuses are: water scarcity, long-term drought, and the impacts of climate change (e.g. changes in rain regimens, increase in atmospheric temperatures and wildfires, among others). This paper shows the efforts done by the institution in terms of new constructions of green/smart infrastructure, water management, use of renewable energy—to take advantage of its location and climate, and waste management programs. The installed solar photovoltaic capacities (1.2 MW) makes CETYS the academic institution with the largest potential in Latin America. The wastewater treatment plants in Tijuana and Mexicali campus reduce significantly the amount of new water required, and finally, the “Zero Waste” program has given excellent results internally, which has allowed CETYS to expand this experience and provide service to the community that surrounds the Tijuana campus. Through these dimensions of analysis, this paper tries to show CETYS’ commitment to sustainability and its regional leadership around this issue.
CETYS University Commitment to Sustainability. Experiences of a Mexican Private University
Keywords: Sustainability; México; Baja California; Water scarcity; Private university; Campus Ensenada